1994
DOI: 10.2172/1372377
|View full text |Cite
|
Sign up to set email alerts
|

Search for the Top Quark at $\sqrt{s}$ = 1.8-TeV

Abstract: We present a search for the top quark in pp-collisions at Vs 1.8 TeV using the CDF detector at the Fermilab Tevatron Collider. We use 21.4 pb-1 of data collected during the 1992-93 Collider Run. In the minimal Standard Model, the top quark decays to a W boson and a b quark. To separate top events which decay into a lepton and jets from the W + multiet background, we identify b quarks via their semileptonic decays. In the W 3 or more 'et sample, we observe 7 events with an estimated background of 31 ± 03.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study conducted by a Korean group recorded a median time of 53 minutes for ESD, whereas another study by a Western country had a median time of 105 minutes. (13,14) The present study had median time of 80.9 minutes. Our results also showed that larger lesions required a longer procedure time.…”
Section: A 2bmentioning
confidence: 89%
“…A study conducted by a Korean group recorded a median time of 53 minutes for ESD, whereas another study by a Western country had a median time of 105 minutes. (13,14) The present study had median time of 80.9 minutes. Our results also showed that larger lesions required a longer procedure time.…”
Section: A 2bmentioning
confidence: 89%